Multiparisitism in feline domestic, case report (Research, Society and Development, 2020)
Domestic cats are increasingly living with humans, gaining more space and being part of the family structure, as their personality and behavior, allows them to easily adapt to the routine of the modern population. Because they are closer, some care must be taken, aiming at the health of these animals and also of man, since many agents that can affect cats, have zoonotic potential. The fecal sample of an adult feline was analyzed, with loose stools, with streaks of blood and perianal itching, with the presence of erythema in this region. The coproparasitological techniques used for the diagnosis were: Willis-Mollay (1929), Faust et al. (1938) and Hofmann, Pons and Janer (1934). After analyzing the material, it was found that the animal was parasitized, with the helminths Ancylostoma spp., Toxocara spp. and Dipylidium caninum, in addition to the protozoa, Giardia spp. and Cystoisospora spp. From the diagnosis, treatment was instituted to eliminate these agents. After the end of the therapy, a new analysis was carried out, in which it was found that there was no longer the presence of any type of parasite.